The Best Interests of the Child Principle - Garayová, Lilla (Central European Academy Law Review, 2025)
The best interest of the child principle, a pillar of international family law and children’s rights, is enshrined in the UN Convention on the Rights of the Child and serves as a guiding framework for decision-making affecting children. This article explores the evolution, interpretation, and application of the best interest principle, with a particular focus on the role of the Committee on the Rights of the Child. Additionally, the article highlights historical misapplications of the best interest principle, such as forced adoptions and child migrations, and underscores the risks of vague or biased interpretations. Drawing on Eekelaar’s conceptualisation of children’s basic, developmental and autonomy interests, the article emphasises the need for a child-centred approach.